Establishment and validation of a didactic musculoskeletal ultrasound course for dermatologists using an innovative handheld ultrasound system – the MUDE study (Musculoskeletal Ultrasound in Dermatology). (25th November 2021) - Grobelski, Jakub; Recker, Florian; Wilsmann‐ Theis, Dagmar; Hartung, Wolfgang; Karakostas, Pantelis; Brossart, Peter; Schäfer, Valentin Sebastian
Summary: Background: In the early detection of arthritis, such as psoriatic arthritis, musculoskeletal ultrasound (MSUS) of painful joints plays an important role in diagnosis. Pathological findings can be missed during clinical examination, especially if conducted by physicians who are not trained. The objective of this study was to examine a pilot MSUS course designed specifically for dermatologists, the MUDE protocol. Methods: To assess the degree of MSUS expertise of the participants, a questionnaire using SurveyMonkey ® was completed before the course. The course concept covered only the most important ultrasound sections of all joints and focused on the detection of joint effusion and hyperperfusion. The course consisted of three modules and was carried out over six months. The portable Butterfly IQ ® system in combination with an Apple iPad was provided to enable practice between the courses. The final teaching evaluation was carried out as an objective structured clinical examination (OSCE). Results: Twelve dermatologists participated. The survey revealed no prior knowledge of MSUS. The overall score of all participants in the OSCE was 21.86 (87.44 %) out of a total of 25 points, which corresponded to the school grade good. Conclusion: The innovative MUDE protocol is thus particularly suitable for the training of dermatologists in MSUS, irrespective of prior knowledge.